2020
DOI: 10.3390/ijerph17082708
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Mental Disorder Symptoms among Canadian Public Safety Personnel

Abstract: Poor sleep quality is associated with numerous mental health concerns and poorer overall physical health. Sleep disturbances are commonly reported by public safety personnel (PSP) and may contribute to the risk of developing mental disorders or exacerbate mental disorder symptoms. The current investigation was designed to provide estimates of sleep disturbances among PSP and explore the relationship between sleep quality and mental health status. PSP completed screening measures for sleep quality and diverse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Approximately 10-30% of the population worldwide suffer from insomnia [2]. It has been shown that insomnia is associated with considerable deterioration of quality of life, higher prevalence of depressive disorder, cognitive impairment and higher risk of work absenteeism [3][4][5]. In addition, insomnia is generally associated with a variety of medical conditions, such as diabetes, heart disease, migraine and cancer [6][7][8][9], even higher risk of mortality [10].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10-30% of the population worldwide suffer from insomnia [2]. It has been shown that insomnia is associated with considerable deterioration of quality of life, higher prevalence of depressive disorder, cognitive impairment and higher risk of work absenteeism [3][4][5]. In addition, insomnia is generally associated with a variety of medical conditions, such as diabetes, heart disease, migraine and cancer [6][7][8][9], even higher risk of mortality [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, "Drug side effects" means that the patients are experiencing severe side effects compared to other medications. Side effects appear differently depending on the type of medication, but side effects such as drug dependence, insomnia, fatigue, aggression, decreased concentration, decreased memory, drowsiness, and suicidal thoughts mainly appear in the drugs commonly consumed by PD patients [9,39,40]. The side effects differ depending on the type and dose of the drug, and this should be thoroughly discussed with a doctor.…”
Section: Nevertheless Physical Activity Is a Challengementioning
confidence: 99%
“…Although the definition of mental health is not uniform in academic circles, the research significance of mental health is self-evident. Mental health has been widely used in psychology ( 1 ), sociology ( 2 ), psychiatry ( 3 ), pedagogy ( 4 , 5 ), genetics ( 6 ), and other fields.…”
Section: Introductionmentioning
confidence: 99%